How Directors' Prior Experience with Other Demographically Similar CEOs Affects Their Appointments onto Corporate Boards and the Consequences for CEO Compensation - Zhu, David H.; Westphal, James D. (Academy of Management Journal, 2014)
In recent years, new director appointments have increasingly posed a dilemma for corporate leaders: while CEOs prefer individuals who have similar backgrounds to them, they face increased pressure to appoint new directors who have a different demographic profile. We suggest that CEOs may resolve this dilemma by appointing new directors who have prior experiences working with other demographically similar CEOs. We then explain why this tendency is stronger when new directors are demographically more different from CEOs. Moreover, we posit that new directors' prior experiences with other similar CEOs will reduce the negative effect of their demographic differences from the CEO on CEO compensation. Longitudinal analysis of Fortune 500 companies' new director appointments and subsequent CEO compensation provided support for our theoretical expectations. This study identifies an important new role that interlock ties to other CEOs can play in corporate governance and leadership. In particular, we suggest that such ties are a means by which CEOs evaluate whether a new director will support their leadership and decision making. In explaining the role of directors' ties to other CEOs in influencing director appointments and CEO compensation, this study also highlights the important influence of triads on CEO-director dyadic relations.